The International IT Standardization System, Its Role in the Development of the Information Industry and Its Operating Principles - Vladimir Sukhomlin (Современные информационные технологии и IT-образование, 2022)
The article covers the review of the modern system of international standardization in the field of information technology (IT), and the fundamental role of standards in the purposeful development of IT. Standards are important in all areas of activity, but for the IT field, which should be considered as an established scientific and applied discipline, the standards’ system plays a special role - it performs the function of a scientific and methodological basis for the IT field, representing a world of models of different levels of abstraction, including models: conceptual, architectural, functional, data, behavioral, relationships, management processes for various activities, as well as a huge set of standardized methods and tools for processing data, information and knowledge. And this world of models serves as a conceptual, scientific and instrumental basis for the further development of the IT field. Meanwhile, many of these standardized models determine the fundamental laws of information matter. In this regard, it is extremely important for university students to study the principles of building and functioning of the international standardization system in the field of IT, to study the fundamental standards for the most important areas of IT, as well as to study the system standards of the International Organization for Standardization ISO. The article discusses the structure of the international standardization system, including: official international standardization organizations (ISO, IEC, IUT), regional standardization organizations (for example, CEN, CENELEC, ETSI); national standards organizations (ANSI, AFNOR, BSI, DIN, JISC, etc.), industry consortia and professional organizations (ISOC, IAB, IETF, IRTF, IEEE, OMG, ECMA, W3C, Open Group, WFMC, OCF, ONF, Foundation SFIA, etc.). It describes the standardization processes of a number of organizations, gives examples of standards developed by them.